Landscape effects on nest site selection and nest success of Northern Lapwing Vanellus vanellus in lowland wet grasslands. Issue 1 (2nd January 2017) - Bertholdt, Nikolas P.; Gill, Jennifer A.; Laidlaw, Rebecca A.; Smart, Jennifer
ABSTRACT: Capsule: Northern Lapwing Vanellus vanellus avoid nesting close to small woodland patches but nest predation rates do not vary with distance to woodland patches, either because risky areas are avoided or perceived nest predation risk does not reflect actual risk. Aims: To explore the effects of woodland patches in wet grassland landscapes on nest distribution and success of Lapwings. Methods: We quantified the effect of woodland patches on the distribution and outcome of Lapwing nests across four wet grassland sites by mapping nest distribution and monitoring nest outcomes. Results: Lapwing nested significantly further from woods than expected by chance. Neither nest predation rates nor the probability of predation occurring at night (thus primarily mammalian predators) or day (primarily avian predators) varied in relation to distance from woodland patches. Conclusions: High levels of nest and chick predation in wet grassland landscapes limit the capacity for breeding wader populations to be self-sustaining. Consequently, identifying manageable landscape features that influence predation rates is an important focus of conservation research. Lapwing avoid breeding close to woodland but, as nest predation rates do not vary with distance from woodland patches, their removal may increase the area of suitable nesting habitat but is unlikely to substantially influence productivity.